Potentiality of alternative irrigation regimes to mitigate greenhouse gas emissions from Malaysian paddy rice cultivation - Pauzai, Nur Fitriah (2022)
Rice is an important food source and is the third-largest consumed grain worldwide. However, the production of rice under continuous flooding (CF) paddy fields is a primary anthropogenic source of methane (CH4) gas, one of the major greenhouse gases (GHG) that contributes to global warming. Alternate wetting and drying (AWD) and mid-season drainage (MD) are two alternative irrigation regimes for rice paddies that can potentially reduce CH4 emissions from rice cultivation. The principle behind these two irrigation regimes is water level in the soil will be lowered, and the soil will be exposed to oxygen, shifting the soil to an aerobic state and hence retarding the production of CH4 by soil methanogens. However, exposing the soil to oxygen may increase nitrous oxide (N2O) emissions, another significant GHG more potent than CH4. The present study was carried out to measure and compare GHG emissions of rice planted under CF, AWD, and MD practices, the soil microbial diversity and abundance of each irrigation practice, and its effect on rice plant physiology and grain yield. Rice (Oryza sativa var. MR297) was transplanted into 15 tanks, assigned equally to the three treatments: AWD, MD, and CF, and arranged in a randomized complete block design. The soil used in this study was taken from a rice field in Pendang, Kedah. Emissions of GHG were measured weekly using static chambers, and the sampled air was analyzed for CH4 and N2O concentrations using gas chromatography. Soils were sampled on the 58th and 96th day after transplant (DAT) from each treatment to assess their microbial diversity and abundance using 16S rRNA microbiome sequencing. Rice plant height, leaf area, and greenness were measured weekly, while 1000-grain weight and total plant biomass dry matter were measured after harvest. Leaf photosynthesis rates were measured during the rice plant's reproductive, flowering, and ripening stages to measure plant water stress and water use efficiency. Leaf samples were analyzed for δ13C isotope composition to determine water stress in plants. This study found that rice plants under alternative irrigation regimes do not undergo plant water stress due to water scarcity. The photosynthesis rate shows a similar pattern between the treatments, and the carbon isotope composition shows a negative value under CF, MD, and AWD on the 78th and 96th DAT. The CH4 emissions from CF, AWD, and MD were 70.24, 30.75, and 15.93 g CH4 m−2 for CF, AWD, and MD, respectively. The methane emissions from MD and AWD were 77.07% and 57.81% lower, respectively, then CH4 emissions from CF. On the other hand, MD and AWD did not emit N2O fluxes throughout the planting period. Methanogenic microbes were found abundant in the CF soil samples, while methanotroph microbes were abundant in CF and MD soil samples. CF, MD, and AWD presented 82.74, 86.59, and 67.02 kg m-2 of grain yield, with no significant differences between the treatments. Besides, alternative irrigation regimes do not affect rice plant height, leaf area, and greenness index between the treatments. The present study demonstrated that alternative irrigation regimes when applied to Malaysian rice soil planted with Malaysian rice variety did not cause any reduced crop performance and yield, at the same time, were proven to reduce emissions of GHG.